2018
DOI: 10.3389/fpsyg.2018.00888
|View full text |Cite
|
Sign up to set email alerts
|

Expressive Morphological Skills of Dual Language Learning and Monolingual German Children: Exploring Links to Duration of Preschool Attendance, Classroom Quality, and Classroom Composition

Abstract: A growing body of research has been documenting environmental factors that support preschoolers’ vocabulary skills. However, less is known about how environmental factors are related to morphological skills of dual language learners (DLLs) and single language learners (SLLs). We examined connections with preschool experiences by investigating the effects of duration of preschool attendance, classroom quality, and classroom composition variables (percentage of DLLs and percentage of children from families with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…1 Still, ECEC centers tend to be highly segregated regarding children's socioeconomic and ethnic background (Becker & Schober, 2017;Gambaro, 2017). While there are differences between individual ECEC centers, overall Germany is linguistically highly diverse and ECEC centers are attended by children exposed to numerous respective heritage languages at home (Bihler, Agache, Schneller, et al, 2018). The ethnic composition of ECEC centers reflects residential segregation.…”
Section: Ecec In Germanymentioning
confidence: 99%
See 1 more Smart Citation
“…1 Still, ECEC centers tend to be highly segregated regarding children's socioeconomic and ethnic background (Becker & Schober, 2017;Gambaro, 2017). While there are differences between individual ECEC centers, overall Germany is linguistically highly diverse and ECEC centers are attended by children exposed to numerous respective heritage languages at home (Bihler, Agache, Schneller, et al, 2018). The ethnic composition of ECEC centers reflects residential segregation.…”
Section: Ecec In Germanymentioning
confidence: 99%
“…Research on classroom composition in Germany is scarce and findings are inconsistent. Regarding composition in terms of DLLs or children with immigrant background, several studies found no associations with individual language skills (Bihler, Agache, Schneller, et al 2018; Kohl et al, 2019; Willard et al, 2019), while others found that the percentage of DLLs or children with immigrant background was negatively linked to children’s language skills (Biedinger & Becker, 2010; Ebert et al, 2013; Klein & Becker, 2017; Niklas et al, 2011). Similarly, some studies on composition in terms of children’s socioeconomic background yielded no significant associations with language skills (Biedinger & Becker, 2010; Kohl et al, 2019), while other studies did find connections (Bihler, Agache, Schneller, et al, 2018; Niklas et al, 2011).…”
Section: How Do Peer Effects Operate?mentioning
confidence: 99%
“…To our knowledge, there are three German studies focusing on differences between SLLs and DLLs: two studies based on broader measures of ECEC quality (Environmental Rating Scales) suggest that ECEC quality is connected to young DLLs’ but not SLLs’ German vocabulary skills (Ebert et al, 2013; Willard, Agache, & Leyendecker, 2019); a third study examined links between interaction quality as measured with the CLASS and children’s morphological skills and yielded similar results. Quality was linked to German morphological skills for DLLs but not SLLs (Bihler, Agache, Schneller, Willard, & Leyendecker, 2018). In the present study, we examined whether ECEC classroom process quality, on the level of actual interactions, is differently connected to SLLs’ and DLLs’ German vocabulary.…”
Section: Ecec Process Quality and Children’s Language Skillsmentioning
confidence: 99%
“…Centers also differ in their ethnic and linguistic composition, but there is a relatively high level of segregation, and DLLs are more likely to attend centers where the majority of children are also DLLs (Becker & Schober, 2017; Gambaro, 2017). Yet, in most ECEC centers, teachers speak solely German with the children (Bihler, Agache, Schneller, et al, 2018). Comparably low costs mean that income is likely to have little impact on the age at which a family enrolls their child and on the center they choose.…”
Section: Ecec In Germanymentioning
confidence: 99%
“…Importantly, there is evidence that the domains do not have the same predictive validity for all children. For example, a recent study reported that instructive interactions were positively related to dual language learners’ German morphological skills, whereas they were not for monolingual German children ( Bihler et al, 2018 ). Thus, appropriately investigating predictive validity is beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%